Land Use Planning and Environmental Sustainability in Malaysia : Policies and Trends - Hunud Abia Kadouf, Sharifah Zubaidah Al Junid (International Islamic University Malaysia, 2006)
Buku ini berisi tentang perencanaan penggunaan lahan dan kelestarian lingkungan di Malaysia: Kebijakan dan Tren